2018
DOI: 10.1073/pnas.1800851115
|View full text |Cite|
|
Sign up to set email alerts
|

Ancient genomes from North Africa evidence prehistoric migrations to the Maghreb from both the Levant and Europe

Abstract: The extent to which prehistoric migrations of farmers influenced the genetic pool of western North Africans remains unclear. Archaeological evidence suggests that the Neolithization process may have happened through the adoption of innovations by local Epipaleolithic communities or by demic diffusion from the Eastern Mediterranean shores or Iberia. Here, we present an analysis of individuals' genome sequences from Early and Late Neolithic sites in Morocco and from Early Neolithic individuals from southern Iber… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
98
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(118 citation statements)
references
References 37 publications
(39 reference statements)
13
98
1
Order By: Relevance
“…2A and table S8). We replicate previous findings of the arrival of Anatolian Neolithic-associated ancestry in multiple regions of Iberia in the Early Neolithic (7, 8, 12); however, sampling from this period remains limited and studies of larger sample sizes and additional sites will be important in order to shed additional light on the interaction between the incoming farmers and indigenous hunter-gatherers. In the Middle Neolithic and Copper Age, we reproduce previous reports of an increase of hunter-gatherer-related ancestry after 4000 BCE (6, 7, 12, 13), with higher proportions in groups from the north and center.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…2A and table S8). We replicate previous findings of the arrival of Anatolian Neolithic-associated ancestry in multiple regions of Iberia in the Early Neolithic (7, 8, 12); however, sampling from this period remains limited and studies of larger sample sizes and additional sites will be important in order to shed additional light on the interaction between the incoming farmers and indigenous hunter-gatherers. In the Middle Neolithic and Copper Age, we reproduce previous reports of an increase of hunter-gatherer-related ancestry after 4000 BCE (6, 7, 12, 13), with higher proportions in groups from the north and center.…”
supporting
confidence: 80%
“…1C and fig. S3), and like ~3000 BCE Moroccans (8) can be well modeled as having ancestry from both Late Pleistocene North Africans (15) and Early Neolithic Europeans (tables S9–10). His genome-wide ancestry and uniparental markers (tables S1 and S4) are unique among Copper Age Iberians, including individuals from sites with many analyzed individuals such as Sima del Ángel, and point to a North African origin.…”
mentioning
confidence: 99%
“…Although a clear-cut differentiation can also be appreciated for the European component, more frequent among Berbers than Arabs, this was found at a lower frequency than the other two mentioned previously. Sub-Saharan and Near Eastern ancestries, which are known to have been brought to North Africa through a variety of ancient (pre-neolithic and neolithic) and recent (Arab conquest) migratory waves (Newman, 1995;Appiah & Gates, 2010;Henn et al, 2012;van de Loosdrecht et al, 2018;Fregel et al, 2018;Elkamel, Boussetta, Khodjet-El-Khil, Benammar Elgaaied, & Cherni, 2018;D'Atanasio et al, 2018), were found not to vary substantially among the Southern Tunisia ethno-linguistic groups.…”
Section: Discussionmentioning
confidence: 93%
“…2c, Additional file 2: Figure S9- S11). These two genetic ancestries have been intertwined in the northwestern part of the African continent for at least the last 3000 years [55]. Fregel and colleagues (2018) linked the diffusion of people across Gibraltar to Neolithic migrations and the Neolithic development in North Africa [55].…”
Section: Discussionmentioning
confidence: 99%